TACKLING THE CO-EPIDEMIC OF DIABETES AND TUBERCULOSIS: FROM EVIDENCE TO POLICY AND PRACTICE - Mukhtar, Fatima; Butt, Zahid A (Journal of Ayub Medical College Abbottabad, 2016)
With the global increase in the diabetic population there is a resurgence of interest in the dual epidemic of diabetes mellitus (DM) and tuberculosis (TB), which have a bidirectional detrimental relationship with negative consequences for co-infected patients. Pakistan is feared to be hit the hardest, occupying fifth position amidst the 22 high burden TB countries, and ranking seventh in the global diabetic burden. The diabetes tuberculosis treatment outcome (DITTO) study was undertaken to determine the impact of diabetes on tuberculosis treatment outcome in Pakistan. The generation of such scientific evidence is useless if it is not utilized for policy making and practice, especially in a developing country like ours with a dearth of resources. In this paper, we have developed a framework for the transfer of scientific evidence regarding the impact of diabetes on TB treatment outcomes into policy and practice. The framework is divided into three components namely; generation of scientific evidence harnessing international and national efforts, informing health policy and practice and addressing other concerns such as social protection, health education and future research. Keywords:Diabetis, Tuberculosis, Policy, epidemic